The great archaeologists - Fagan, Brian M. (Thames & Hudson, 2014)
Organized into six thematic sections, this book gives short biographies and assessments of the achievements of 70 of the worlds greatest practitioners, written by a 40-strong team of contributors, themselves all eminent archaeologists and authors.